UPAYA PEMERINTAH DAERAH DALAM MENINGKATKAN KESEJAHTERAAN SOSIAL LANJUT USIA NON POTENSIAL: Studi Aksesibilitas Pelayanan Umum pada Bandara Sultan Thaha Provinsi Jambi - Sari, Nova Kurnia (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2017)
Life expectancy of the Indonesian population is increasing, affecting the number of elderly who is growing. This creates a dilemma for the government, to be a good achievement but also to increase the number of dependence. Especially non-potential elderly who can not live independently and need the help of others in meeting their needs so that a new problem if not handled appropriately. The findings around the authors regarding the state of elderly non-potential that is far from the expression of prosperous and less noticed by many parties, makes the author's reason to be interested in researching, observing and analyzing more about the efforts made by local governments, especially in the provision of accessibility of public services for elderly non potential at Sultan Thaha Airport Jambi Province. This research uses Social Welfare Theory, Local Government and Public Service. Type of research using Qualitative approach. Data collection was done by unstructured in-depth interviews conducted at three different locations. Methods of data analysis in this study by using Creswell analysis model. The results showed that the efforts made by local governments in improving the social welfare of non-potential elderly are still not maximized. Evidenced by the results of interviews and observations that indicate that there are still many non-potential elderly complain about the accessibility of public services at the airport Sultan Thaha Jambi Province as well as lack of coordination between cross-sector local government with relevant agencies that became one of the factors causing it to happen.